Fleas associated with non‐flying small mammal communities from northern and central Chile: with new host and locality records. Issue 4 (18th March 2013) - BAZÁN‐LEÓN, E. A.; LARESCHI, M.; SANCHEZ, J.; SOTO‐NILO, G.; LAZZONI, I.; VENEGAS, C. I.; POBLETE, Y.; VÁSQUEZ, R. A.
Abstract: Fleas associated with small mammals from seven localities from northern and central Chile were assessed. We captured 352 small mammals belonging to 12 species from which we obtained 675 fleas belonging to 15 different species. The most frequently captured flea species were Neotyphloceras crassispina crassispina ( n = 198) and N. chilensis ( n = 175). High values of flea species richness and diversity were found in Fray Jorge National Park (NP), a north‐central Chilean site, whereas the highest values of mean abundance (MA) and prevalence were found in three diverse sites that include Los Molles River, a high altitude site located in north‐central Chile, Fray Jorge NP and Dichato, in south‐central Chile. On the other hand, high values of flea richness and diversity were found on two rodent species, Abrothrix olivacea and A. longipilis, whereas the highest values of MA and prevalence were found on Oligoryzomys longicaudatus, A. longipilis and Phyllotis xanthopygus . A total of three new host recordings, nine new localities and nine new host species and locality recordings are reported. Also, this study represents the first known record of Tetrapsyllus ( Tetrapsyllus ) comis in Chile and the first ecological analysis of Neotyphloceras chilensis .